Moment Tensor Components with Their Corresponding Eigen Values and Eigen Vectors for Earthquakes Mw ≥ 6.0 in Northern and Southwestern of Pakistan - Shahzada Khurram; Perveiz Khalid (ASEAN Journal of Science and Engineering, 2021)
Self-generated earthquake catalogue of Mw≥6.0 upto 300 km depth was prepared for the inversion of six components of moment tensor. Seismotectonic map was drawn with seismicity distribution. The stress map of Pakistan was generated through CASMO which described by the Anderson model (1951). The maximum horizontal stress (SHmax) acting in the compressional zone generates reverse faulting (RF) causes to form the three distressing mountainous range called Karakorum, Hindukush and Himalayan i-e SHmaxSHmin. In eastern side of Pakistan, minimum horizontal stress (SHmin) acting in the extensional zone produced normal fault (NF) i-e SHmax SHmin. Focal mechanism was also drawn using source parameters of each event obtained by matlab codes. Stress tensor components were obtained using mathematical equations and out comes were written in the form of 3x3 matrix. All matrices have non trivial solutions and their solution sets were also evaluated in the form of eigen values and eigen vectors. Crustal thickness was displayed by thickness map. The maximum thickness of curst in northern Pakistan i-e 60-70 km whereas in southwestern region this varied from 20– 40 km all around.  This variation due to plate motion intensity and velocity of Indian and Eurasian plate collision.